Media Pembelajaran Interaktif Pengelolaan Sampah Organik, Anorganik dan Bahan Beracun Berbahaya Berbasis Flash - Suseno, Edwin; Purba, Kristo Radion; Intan, Rolly (Jurnal Infra, 2016)
The background of making trash management program is because people are still not able to understand the kinds of trash and how to process the trash properly, so it is not uncommon to people wrongly in processing trash. So in this thesis made a Flash-based interactive learning media. This instructional media created with the aim to help the learning system with visualization methods that aim can increase interest in learning because of the games, quizzes and animations that have been produced.This application uses the supporting software such as Adobe Flash Professional CS 6 to process animation, ActionScript 3.0 for manufacturing feature and Illustrator programs to assist in the design process. For information on trash management obtained from the media in the form of books or the Internet.The results of this thesis is provide information to public about trash management by type. There are also features games and quizzes that help remind about the trash management information so that the public can be tested of understanding will be learning this trash management.